Capacidade de rotação de rótulas condicionadas no concreto armado, com e sem força axial - Agostinho, Paulo Cesar Primo (1986)
The objective of this work was to research, conditioned beam's comportment at the compressed region, wotking to the compound flexion, was realized an previous analysis of the experiment related at the specializes bibliography, whether at the simple flexion, or at the compound flexion. The experimental results were obtained confronted with the values furnished by diferent formules proposed by various laboratorys and authors. As a conclusion of the study was verified that simple expressions of the plastic hingings, translate with enough fidelity the real comportment of the assaied beams.